2014
DOI: 10.3906/vet-1309-79
|View full text |Cite
|
Sign up to set email alerts
|

Meat quality characteristics in Kıvırcık lambs

Abstract: IntroductionSheep production has a significant share in the animal protein market and there are various factors affecting meat quality (1-3). Although lamb is considered fattier than other meats by a lot of consumers, its fat content is not regarded as a problem as it gives tenderness and more flavor to the meat. However, improper rearing and/ or feeding conditions might cause excessive fattening, which reduces demand from customers. In recent years, the production of lamb, which is preferred by the majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
7
19
1
2
Order By: Relevance
“…The mean percentage of proximate principles and fatty acid profile of Bandur ram lamb meat observed in the the present study (Table 7) were similar to the earlier findings in Suffolk Down suckling lamb (Perez et al, 2002), Dorper sheep (Tshabalala et al, 2003), Awassi ram lambs (Abdullah and Qudsieh, 2008) and Kivircik lambs of Turkey (Yarali et al, 2014). Further, the meat had almost equal proportion of unsaturated and saturated fatty acids.…”
Section: Chemical Composition Of Meatsupporting
confidence: 79%
See 3 more Smart Citations
“…The mean percentage of proximate principles and fatty acid profile of Bandur ram lamb meat observed in the the present study (Table 7) were similar to the earlier findings in Suffolk Down suckling lamb (Perez et al, 2002), Dorper sheep (Tshabalala et al, 2003), Awassi ram lambs (Abdullah and Qudsieh, 2008) and Kivircik lambs of Turkey (Yarali et al, 2014). Further, the meat had almost equal proportion of unsaturated and saturated fatty acids.…”
Section: Chemical Composition Of Meatsupporting
confidence: 79%
“…Similar pH values (6.61 ± 0.101) were obtained for Longissimus thoracis et lumborum muscle in Kivircik ram lamb of Turkey (Yarali et al, 2014). However, lower pH of 5.96, 5.93 ± 0.09 and 5.56 were observed in meat of Garole sheep (Banerjee et al, 2009), yearling sheep (Sen et al, 2004) and suckling lambs (Sanudo et al, 2012), respectively.…”
Section: Meat Quality Traitssupporting
confidence: 50%
See 2 more Smart Citations
“…An important question that has to be addressed in a breeding program is the choice of the genotypes or breeds that could be improved by selection. In a recent study, it was shown that Kivircik lambs, which are raised mainly in the western Anatolian region of Turkey (Yarali et al, 2014), have a high quality of meat in terms of several meat quality characteristics (Ekiz et al, 2009). Knowledge of genetic variation and covariation among traits of interest is required for the design of effective sheep breeding programs, the accurate prediction of genetic progress from these programs and to obtain accurate breeding value estimates (Safari et al, 2005).…”
Section: Introductionmentioning
confidence: 99%